Electroencephalographic and behavioral effects of intracerebroventricular or intraperitoneal injections of toxic honey extract in adult Wistar rats and GAERS - ONAT, FİLİZ; KARAMAHMUTOĞLU, TUĞBA (SPRINGER-VERLAG ITALIA SRL, 2014)
Toxic honey, containing grayanotoxin, is obtained from nectar and polen of rhododendron. Consumed in excess it produces seizures and convulsions. In order to investigate whether the toxic honey extract can be used as a seizure model, we examined the electroencephalographic (EEG) and motor effects of intracerebroventricular (icv) or intraperitoneal (ip) injection of toxic honey extract in Wistar rats or in genetic absence epilepsy rats from Strasbourg (GAERS). Male Wistar rats or GAERS were stereotaxically implanted with bilateral cortical recording electrodes in all ip groups and cannula in the icv groups. Based on the previous study, an extract was obtained from the non-toxic and toxic honey. After the injection of the non-toxic or toxic honey extract, seizure stages and changes in EEG were evaluated from 9 am to noon. The icv administration of toxic honey extract produced stage 4 seizures and bilateral cortical spikes within 30-60 min and these effects disappeared after 120 min in Wistar rats or GAERS. The mean of bilateral cortical spike acitivity in EEG of Wistar rats was 804.2 +/- A 261.0 s in the 3-h period. After the icv administration of toxic honey extract to GAERS, the mean duration of spike-and-wave discharges (SWDs) in GAERS significantly decreased during the first 60 min and then returned to baseline level. Ip injection of toxic honey extract caused no seizure and no change in EEG in either GAERS or Wistars. These results suggest that the icv administration of toxic honey extract can be used as a seizure model.
Keywords: Grayanotoxin; Absence epilepsy; Absence seizure; Mad honey; GENETIC ABSENCE EPILEPSY; MAD HONEY; SEIZURES